(untitled) (Bangladesh Journal of Urology, 2020)
Background: The primary aim of the medical therapy for BPH is to improve quality of life by relieving the lower urinary tract symptoms and prevent complications. Objectives: To compare efficacy and safety of double dose of tamsulosin monotherapy with combination of conventional dose of tamsulosin and finasteride in symptomatic BPH. Methods: This was a prospective study carried out in the Department of Urology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh during the period of July 2005 to June 2006. Total 60 patients of 45-80 years of age were consequently selected according to inclusion criteria. After completion of baseline clinical evaluation and investigations, participants were divided into two groups, group A and group B. Group A were given tamsulosin 0.4 mg for 1 week. Then double dose of tamsulosin (0.8 mg) were given from 2nd week for 12 months. Group B were given tamsulosin 0.4 mg and finasteride 5 mg for the same duration. Efficacy was evaluated at 6 month and 12 month follow up visit and a comparison was made between them. During follow up each was observed for any adverse effect. The parameters monitored were International Prostate Symptom Score (IPSS), Maximum urine flow rate (Qmax), Post Voidal Residual Volume (PVR) and Prostate volume. Results : Both double dose of tamsulosin 0.8 mg and combination of conventional dose of tamsulosin 0.4 mg and finasteride 5 mg are effective in relieving symptoms of BPH but combination dose is superior to double dose monotherapy. Outcome parameters at end point follow up after 12 months showed significant improvement of IPSS (p<0.05), PVR(p<0.001), Q max (p<0.001) and prostate volume (p<0.001) in combination group than double dose group .The incidence of adverse events were also significantly less in combination group (p<0.05). Conclusion: Combination of conventional dose of tamsulosin with finasteride appears to have more efficacy and safety than double dose of tamsulosin in symptomatic BPH. Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.94-98